Study on the Influence Factors of Surrounding Tunnel Longitudinal Deformation Caused by Pit Excavation Based on Nonlinear Pasternak Modeling - Honghua Zhao; Yutao Song (Buildings)
In practical engineering, it is often necessary to constructed deep pits next to tunnels. So it is crucial to evaluate surrounding tunnels deformation and stress to ensure their safe operation. Pasternak soil model that considers soil nonlinear is adopted to solve tunnel beam’s differential equation to obtain longitudinal tunnel deformation and stress. The rationality of considering soil nonlinear methods was verified by contrasting measured with calculated results. On this basis, a comparative study was conducted on the calculation and analysis of various influencing factors based on engineering examples. It shows that the longitudinal tunnel deformation reduces with increase of soil modulus, tunnel axis and pit long side angle, tunnel stiffness reduction coefficient, tunnel axis and pit center horizontal distance. When discrete length of tunnel is less than 5 m, calculated value of longitudinal tunnel deformation changes little with discrete length. When pit depth increases, maximum longitudinal tunnel deformation also increases gradually. When tunnel buried depth gradually increases in the range of 1.5~3.9 times pit depth, maximum longitudinal tunnel deformation reduction rate becomes small. Similar pro-jects construction methods can refer to the results, and it have certain practical application value of engineering.